Opsoclonus-Myoclonus Syndrome Associated With West-Nile Virus Infection: Case Report and Review of the Literature - Radu, Răzvan Alexandru; Terecoasă, Elena Oana; Ene, Amalia; Băjenaru, Ovidiu Alexandru; Tiu, Cristina (Frontiers in Neurology, 2018)
Opsoclonus-myoclonus syndrome (OMS) is a very rare condition with different autoimmune, infectious and paraneoplastic aetiologies or in most cases idiopathic. We report the case of a 75-year-old woman who was admitted in our department in early fall for altered mental status, opsoclonus, multifocal myoclonus, truncal titubation and generalized tremor, preceded by a five day prodrome consisting of malaise, nausea, fever and vomiting. Brain computed tomography and MRI scans showed no significant abnormalities and cerebrospinal fluid changes consisted of mildly increased protein content and number of white cells. Work-up for paraneoplastic and autoimmune causes of OMS was negative but serologic tests identified positive IgM and IgG antibodies against West Nile virus (WNV). The patient was treated with Dexamethasone and Clonazepam with progressive improvement of mental status, myoclonus, opsoclonus and associated neurologic signs. Six months after the acute illness she had complete recovery. To our knowledge this is the 14th case of WNV associated OMS reported in the literature so far. We briefly describe the clinical course of the other reported cases together with the different treatment strategies that have been employed.